EKSPLORASI TUMBUHAN OBAT DI HUTAN PENELITIAN UNIVERSITAS BORNEO TARAKAN SEBAGAI BAHAN AJAR BERUPA BOOKLET UNTUK SISWA KELAS X SMK KESEHATAN KALTARA TARAKAN - Alfrida Alfrida; Darius Rupa; Endik Deni Nugroho (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2020)
This study aimed to determine the types of medicinal plants in the forest area of the Borneo Tarakan University and produce a product in the form booklet that are suitable for use. The type of this research was Research and Development (R D) which uses the development model of Borg and Gall (1983) and is only carried out up to the fifth stage. The results showed that 15 species were found, Kayu putih (Melaleuca leucadendron L.), Paku picisan (Drymoglossum pilloselloides L.), Karamunting (Melastoma malabathricum L.), Resam (Dicronopteris linearis L.), Pandan (Pandanus Sp.), Paku kawat (Lycopodium cernuum L. ), Congkok (Molineria capitulate L.), Jintan (Plectranthus amboinicus L.), Kantong semar (Nepenthes ampullaria), Anggrek tanah (Bromheadia finlaysoniana L.), Hiring-Hiring (Scleria sumatrensis Retz.), Lengkuas (Alpinia galangal L.), Paku tanduk (Platycerium bifurcatum), Paku sarang burung (Asplenium nidus L.), Paku kasak (Blechnum orientale L.). The result of research development in the form booklet were resulted scores validation from that are 86.6% (very feasible), material experts at 80% (feasible), practitioners at 100% (very feasible) and the percentage of student response tests at 94.5% (very interesting. The concluded of this research is the medicinal booklet with medicinal properties in the Borneo Forest Tarakan Research Forest Area is feasible to be used as teaching material for grade X SMK students.Keywords: Medicinal Plants, Booklet